Commercially Important Medicinal Plants of South Africa: A Review. (27th December 2013) - Street, R. A.; Prinsloo, G.
Abstract : There is a growing interest in natural plant-based remedies as a source for commercial products. Around 80% of the South African population use traditional medicines to meet their primary health care needs; however, only a few South African medicinal plants have been exploited to their full potential in terms of commercialization. The opportunity for bioprospecting of plant compounds for novel pharmaceuticals remains largely untapped. Certain renowned medicinal plants of international acclaim including buchu and rooibos are currently contributing to local enterprise; however, other exciting opportunities exist for commonly used plants which have not yet reached the international arena. This paper focuses on the key research and development contributions of 10 commercially important medicinal plants of South Africa. Traditional uses, scientific validation, commercialisation developments, as well as both potential opportunities and setbacks are discussed.